Draft Annual Plan (2008-09) and 11th Five Year Plan (2007-12) Part-III Government of Tripura - Planning Commission (Planning Commission, 2008)
GN Statement Draft Annual Plan-2008-09 Proposed Outlays Draft Annual Plan 2008-09 Proposed Outlays (Scheme-wise) Physical Targets and Achievements, Statement Regarding Externally, Aided Projects Bharat Nirman Programmes Centrally Sponsored Schemes Draft Annual Plan 2008-09 -Financial Outlays : Proposals for TSP Draft Annual Plan 2008-09-PhysicalTargets and Achievements :Proposals for TSP Draft Annual Plan 2008-09-Financial Outlays : Proposals for SCSP raft Annual Plan 2008-09-Physical Targets & Achievements : Proposals for SCSP A Draft Annual Plan 2008-09-Financial Outlays : Proposals for WC.
Planning (P&C) Department